From Commitment to Disengagement: How the Tenure-Track System Shapes Early-Career Faculty Teaching Engagement in China - Wang, Yajing (Journal of University Teaching and Learning Practice, 2025)
This study explores how the tenure-track system (TTS) affects early-career faculty teaching engagement in Chinese public universities. Drawing on Career Development Theory and Role Theory, and using Interpretative Phenomenological Analysis (IPA) of twelve interviews, the study identifies a three-stage trajectory: initial commitment, strategic recalibration, and eventual disengagement. Faculty experienced role conflict intensified by research-centred evaluation metrics and student evaluation pressures, leading to a gradual shift from meaningful teaching to perfunctory instruction and grade inflation. Rather than signalling motivational decline, disengagement emerges as a strategic adaptation to institutional incentives. The study contributes to theoretical understandings of academic identity negotiation under performance-driven regimes and highlights the need for diversified, formative-oriented evaluation systems that value both research and teaching contributions. Practical implications for tenure-track reforms in China and comparable higher education contexts are discussed.